Co-creating a repository of best-practices for collaborative translation - Désilets, Alain; van der Meer, Jaap (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Collaborative translation has the potential for significantly changing how we translate content. However, successful deployment of this kind of approach is far from trivial, as it presents potential adopters with a rich and complex envelope of processes and technologies, whose respective impacts are still poorly understood. The present paper aims at facilitating this kind of decision making, by describing and cataloguing current best-practices in collaborative translation. More precisely, we present a collection of Design Patterns which was created collectively by a small group of practitioners, at a one-day roundtable hosted by the Translation Automation Users Society in October of 2011. This collection has been put on an open wiki site (www.collaborative-translation-patterns.com) in the hopes that other practitioners in the field will refine and augment it.